Same Day Biopsy and Treatment of Non-Melanoma Skin Cancer in Patients with Field Cancerization: A Retrospective Chart Study - Jonathan Miles; Camila Luis-Gronau; Estefania Cruzval-O’Reilly; Aida Lugo-Somolinos; Puneet S. Jolly (Journal of Skin Cancer)
Background. Patients with field cancerization will develop numerous superficial non-melanoma skin cancers (NMSCs). Treating patients with field cancerization can be challenging and burdensome due to the numerous non-melanoma skin cancers (NMSCs) they develop and the frequent dermatology visits required for biopsy and treatment. Objective. The success rate of diagnosing and treating lesions suspicious for NMSCs on the same day is measured, immediately after biopsy. Methods. We retrospectively reviewed records of patients with same day lesion diagnosis and curettage treatment to determine diagnostic accuracy, treatment failure, and number needed to treat to reduce a follow-up treatment. Results. A total of 237 lesions underwent same day biopsy and treatment, of which the majority were NMSC (66%) or actinic keratosis (23%). Patients had at least 3 months and a median of 17 months follow-up. A total of 20 lesions either recurred or were deemed to require additional treatment. The number needed to treat (NNT) to prevent one follow-up treatment was 1.3. Limitations: sample size limited ability to determine risk factors for treatment failure. Conclusion. Simultaneous diagnosis and treatment of superficial NMSCs is a successful way of improving efficiency and patient satisfaction.